Northern sparks innovation, technology policy, and the arts in Canada from Expo 67 to the Internet age - Century, Michael 1955- (The MIT Press, 2022)
"Northern Sparks explores modern Canadian innovation in media arts and technology since 1967, focusing on the intersection of art, science, technology, and policy"--
Keywords: Expo -- 1967 -- Montréal; Geschichte 1967-1992; Innovation; Computerkunst; Medienkunst; Politik; Digitalisierung; Technologie; Kanada; Technological innovations / Canada / History / 20th century; Digital media / Canada / History / 20th century; Technology and state / Canada / History / 20th century; Technology and the arts / History / 20th century; Digital media; Technological innovations; Technology and state; Technology and the arts; Canada; 1900-1999; History